Intraoperative diagnosis of autonomic neuropathy in a case of Charcot–Marie–Tooth disease undergoing laparoscopic cholecystectomy: A case report - Arin, Kazi Mahzabin; Karmakar, Chandra Shekhar; Akhtaruzzaman, AKM (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Not available